The effect of the peer support on stigma among patients with obesity: A quasi-experimental study - Li Wei; Zhang Min; Wang Jun (Science Center Group, 2026)
Background: Obesity is a growing global public health concern that is frequently accompanied by weight-related stigma, which negatively affects psychological well-being, social participation, and engagement in health services. Stigma represents a critical psychosocial barrier in obesity management that is often insufficiently addressed by conventional interventions focusing primarily on behavioral and clinical outcomes. Peer support has emerged as a promising approach to address psychosocial challenges through shared experiences and mutual support in community settings. Objective: This study aimed to examine the effect of peer support on stigma among patients with obesity in a community-based context. Methods: A quasi-experimental study with a pretest–posttest control group design was conducted among adults with obesity recruited from community health programs. Participants were allocated into an intervention group receiving a structured peer support program and a control group receiving usual community-based health education. Stigma was measured using a validated weight stigma instrument before and after the intervention. Data were analyzed using descriptive and inferential statistics to assess within-group and between-group differences. Results: The intervention group demonstrated a significant reduction in overall stigma scores following the peer support program, whereas the control group showed no significant change. Post-intervention stigma levels were significantly lower in the intervention group compared to the control group. Subdomain analysis revealed substantial improvements in internalized stigma and perceived social rejection, with a moderate improvement in emotional distress. The findings indicate a clinically meaningful and statistically significant effect of peer support on stigma reduction. Conclusion: Peer support is an effective community-based intervention for reducing stigma among patients with obesity. The intervention addresses key psychosocial dimensions of obesity by enhancing self-acceptance, emotional support, and social connectedness.Community obesity programs should integrate peer support as a complementary strategy to conventional interventions, and future research should explore long-term outcomes and scalability across diverse populations.